The hospital performance indices after implementing the Universal Health Coverage in the Iran - Reza Khadivi; Mahshid Sadeghi Dehcheshme (Shahid Beheshti University of Medical Sciences, 2020)
Background: The health sector evolution plan (HSEP) was implemented in 2014 in Iran. The aim of present study was to evaluate the hospital performances indices after implementing the second phase of universal health coverage (UHC) comparing to before. Methods: In a cross-sectional study in 2019, the data of 58 hospitals were gathered from database in Statistics' office in clinical deputy of Isfahan University of Medical Sciences (MUI), from 3 years before HSEP implementing to 3 years after that, between 2011 and 2017. Sampling was performed as census method. The data including the inpatient bed count in different type of hospitals (public hospitals affiliated to MUI, not for profit hospitals affiliated to the Social Security Organization (SSO), hospitals affiliated to military organizations, private and charity hospitals), the Bed occupancy rate (BOR), number of inpatients annually and the average length of stay (ALOS) in hospital, were collected and analyzed. Results: By comparing to before carrying out the HSEP, the available beds, particularly in private hospitals was increased significantly (83.22%) after implementing the HSEP. Moreover, the number of hospitalized patients was raised after HSEP, in a way that, the highest percentages have been seen in charity hospitals and private hospitals with the growth rates of 140% and 69.44% respectively. Also, the longest ALOS was seen in public hospitals as likely as 3.4 days. Conclusion: Following the implementing the HSEP, although the available beds and hospitalization rate have been increased significantly, however, the BOR and the ALOS have not been raised markedly.